Digital Education Inequality and Youth Social Mobility in Indonesia’s 3T Regions - M. Badaruddin; Atikah; Finna Khairatun Muhardi; Haldi Jofanda (CV. Get Press Indonesia, 2025)
This study investigates how the lack of digital education access affects youth social mobility in Indonesia's underdeveloped (3T) regions. Using a quantitative analysis of BPS data, the research found significant infrastructural and educational gaps, with 65% of schools lacking internet and 35% lacking electricity. These deficits contribute to low educational attainment, a high 15% dropout rate, and limited opportunities for youth in these areas.Statistical findings confirmed a strong link between digital access and social mobility, with these factors accounting for 62% of the variation in outcomes. The study concludes that building digital infrastructure and improving digital literacy are essential for reducing inequality and fostering inclusive development. This research provides a critical foundation for creating targeted policies and suggests that future studies should explore the long-term impact of these interventions.